2011
DOI: 10.1007/s12032-010-9760-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of panitumumab for metastatic colorectal cancer with wild-type KRAS status: a meta-analysis of randomized clinical trials

Abstract: Panitumumab is a fully human anti-epidermal growth factor receptor (EGFR) monoclonal antibody that has a favorable effect on patients with metastatic colorectal cancer (mCRC) harboring wild-type (WT) KRAS gene. This meta-analysis was planned to quantify the benefit and assess safety. Selected for the analysis were randomized clinical studies that have used panitumumab-based therapy (PBT) for patients with mCRC and where the outcome of patients with WT KRAS was reported. Four eligible studies were analyzed incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…A meta-analysis in 2011 of four randomized clinical studies found significant clinical benefit for panitumumab-based therapy in wild-type KRAS mCRC patients following prior chemotherapy exposure [Ibrahim and Abouelkhair, 2011].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…A meta-analysis in 2011 of four randomized clinical studies found significant clinical benefit for panitumumab-based therapy in wild-type KRAS mCRC patients following prior chemotherapy exposure [Ibrahim and Abouelkhair, 2011].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…As supportive evidence for KRAS exons 2, 3, and 4 testing, ASCO referred to ten meta‐analyses and two health technology assessment reports that reviewed 137 primary studies with 19,543 patients. Table summarizes findings of these ten meta‐analyses.…”
Section: Evidence For Braf Mutations As a Predictive Biomarkermentioning
confidence: 99%
“…This is mainly due to lack of consistent OS benefit when adding anti‐EGFR mAbs to standard of care in the overall and KRAS wt population. In KRAS wt patients, OS benefit was detected in only 6 out of 13 trials .…”
Section: Evidence For Braf Mutations As a Predictive Biomarkermentioning
confidence: 99%
“…For panitumumab, one meta-analysis was assessed [36]. All patients included in the analysis had KRAS WT tumor status.…”
Section: Anti-egfr Therapymentioning
confidence: 99%